(untitled) (Papeles, 2023)
Introduction: The use of information and communication technologies for the acquisition of cross-curricular and teaching competencies in higher education, although common in some areas, has been little studied in the initial training of Early Childhood teachers. The purpose of this study was to analyze the students’ perception of using a WebQuest (WQ) to facilitate the acquisition of cross-curricular and professional competencies in Physical Education in the initial teacher training. Methodology: A quasi-experimental research design with a control group, pretest, and posttest was applied in a Physical Education subject of the Preschool Education Degree. The validated scale for students’ self-perception of competences was used to collect this information. The sample, consisting of 129 students from the Faculty of Education, was divided into two groups. Both received the same methodology, Tutored Learning Projects. One group did it through a WQ, while the other group did not use any web-based methodology. Results and discussion: The results indicated that the use of WQ favoured a greater perception of students in the acquisition of transversal competences. Significant differences were also found between the two groups in the learning of professional teaching competencies. Conclusions: It was found that the WQ resource, after its application, had a positive impact on students in terms of their acquisition of occupational competences.